How working-age population education and health of older people shape the burden of population aging: A comparative study of Macau, Hong Kong, and Singapore - Xue, Dong-mei; Bai, Qian; Bian, Ying (Frontiers in Public Health, 2022)
Macau, Hong Kong and Singapore are all facing increasing population aging. Those aged 65 and over make up the old-age population. The working-age population refers to the population aged 15 to 64. Conventionally, the burden of population aging is measured by the Old-Age Dependency Ratio, which is the ratio of the old-age population to the working-age population. As life expectancy rises, depending exclusively on age to calculate the burden of aging hinders the development of effective anti-aging strategies. The working-age population's education and the elderly's health affect the aging burden's support and generator, respectively. Including them in the calculation gives us a fuller view of the burden of aging. Objective: To compare the population aging burden in Macau, Hong Kong, and Singapore by including working-age population education and elderly health. Results: Hong Kong has the greatest old-age population proportion and Old-Age Dependency Ratio, yet its growth rates are moderate and stable, ranging from 0% to 4% and 0% to 6%, respectively. Macau and Singapore experienced sharper changes in old-age population proportion and the Old-Age Dependency Ratio, with Macau’s Old-Age Dependency Ratio varying between -2.66% and 8.50% and Singapore’s ranging from -1.53% to 9.70%. Three cities showed different patterns in four Education-Health Adjusted Old-Age Dependency Ratio indicators. The Weighted Education-Health Adjusted Old-Age Dependency Ratios are all smaller than the conventional Old-Age Dependency Ratio in the three regions, particularly in Singapore. The Weighted Education-Health Adjusted Old-Age Dependency Ratio of Singapore was reduced by 9.5% to 30.5% compared with the conventional Old-Age Dependency Ratio, that of Hong Kong reduced by 6.2% to 22.5%, and that of Macau reduced by 4.4% to 16.1%. Conclusion: This is the first study to compare the aging burden in Macau, Hong Kong, and Singapore in connection to working-age population education and elderly health. With the new assessment, the burden of population aging in three regions has been reduced, showing that improving the education of the working-age population and maintaining older people's well-being can assist authorities to deal with population aging, especially in Macau and Hong Kong.